Preparation method of molecular sieve catalyst for polymer catalysis

By diversified selection of silicon sources, aluminum sources and template agents and adopting a multi-step preparation process, the problem of unstable catalyst performance in the prior art is solved, and high-purity and diversified customized catalysts are achieved, and their activity, selectivity and service life are improved.

CN119823301APending Publication Date: 2025-04-15广计集团有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510019248.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the choice of silicon source, aluminum source and template agent is single, making it difficult to customize the catalyst, and the introduction of impurities into raw materials with lower purity leads to unstable catalyst performance, reduced activity and selectivity, and shortened service life.

Method used

Ethyl orthosilicate or silicate sol is used as the silicon source, aluminum nitrate, pseudo-thin aluminite or aluminum sulfate is used as the aluminum source, and quaternary ammonium salts of diethylamine, tetrapropyl ammonium hydroxide, and cetyl trimethyl ammonium bromide are used as template agents. The catalyst is prepared through gel preparation, crystallization reaction, ion exchange and modification, molding and other steps to ensure diversified raw material purity and proportion.

Benefits of technology

Customized catalysts are achieved according to different polymer catalytic reaction needs, improving the quality and performance stability of the catalyst, enhancing the stability of metal species in molecular sieve, optimizing the activity and selectivity of the catalyst, extending the service life, and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823301A_ABST
    Figure CN119823301A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a molecular sieve catalyst for polymer catalysis, which comprises the following steps: 1, raw material preparation: selecting 5-15g of tetraethoxysilane as a silicon source; aluminum nitrate is selected as an aluminum source, and the mass of the aluminum nitrate is 2-10 g; the template agent is selected from an organic amine compound, such as diethylamine, and the mass of the template agent is 1-10g; tetraethyl orthosilicate or silica sol can be selected as a silicon source, aluminum nitrate, pseudo-boehmite or aluminum sulfate can be selected as an aluminum source, a template agent covers quaternary ammonium salts of diethylamine, tetrapropylammonium hydroxide and cetyltrimethylammonium bromide, the purity of the raw materials is high, and the high-purity raw materials are beneficial to reducing introduction of impurities and ensuring quality and stability; the preparation method comprises the following steps: preparing a cylindrical or sheet-shaped catalyst blank by a strip extruder or a tablet press, drying at 100-150 DEG C for 12-24 hours, and roasting at 400-500 DEG C for 4-8 hours, so that the prepared catalyst has good mechanical strength and proper shape, is not easy to break or wear, and ensures the stability and operability of the catalyst in production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of molecular sieve catalysts for polymer catalysis, and in particular relates to a preparation method of molecular sieve catalysts for polymer catalysis. Background Art

[0002] Molecular sieves have well-organized pore structure, large specific surface area, surface proton acid centers and cation exchangeability, etc., and are therefore good catalytic materials or catalyst carriers. They have been widely used in catalytic cracking, alkylation, isomerization and other reactions, occupying an important position in the field of catalysis and receiving widespread attention from the industry.

[0003] In the prior art, the selection of silicon source, aluminum source and template may be relatively single, and it is impossible to diversify the selection. The single raw material selection limits the ability to customize the catalyst according to the requirements of different polymer catalytic reactions, and it is difficult to accurately control the catalyst performance. At the same time, raw materials with lower purity may introduce more impurities, which may occupy active sites, affect the formation of crystal structure or interfere with the catalytic reaction process, resulting in unstable catalyst performance, reduced activity and selectivity, and shortened service life. If suitable binders, extrusion aids and lubricants are not selected, the process parameters are not optimized and controlled during the molding process. This may cause the prepared catalyst to have insufficient mechanical strength and inappropriate shape, and it is easy to break or wear in actual industrial applications, thereby reducing the exposure of the catalyst active sites and reducing the activity. Frequent replacement of catalysts will increase production costs and affect the continuity and stability of industrial production. In addition, poor molding process may also affect the pore structure of the catalyst, hinder the diffusion of reactants and products, and reduce the efficiency of the catalytic reaction.

[0004] To this end, we propose a method for preparing a molecular sieve catalyst for polymer catalysis to solve the problems mentioned in the above background technology. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a molecular sieve catalyst for polymer catalysis to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: A method for preparing a molecular sieve catalyst for polymer catalysis, comprising: Step 1: Raw material preparation:

[0007] Silicon source: Use ethyl orthosilicate as the silicon source, with a mass of 5-15g;

[0008] Aluminum source: Aluminum nitrate, with a mass of 2-10g;

[0009] Template agent: organic amine compounds such as diethylamine are selected, with a mass of 1-10g;

[0010] Metal source: transition metal source such as sodium chromate or ammonium molybdate, with a mass of 0.1-2g, used to adjust the activity of the catalyst;

[0011] Solvent: deionized water and sodium hydroxide, the amount of deionized water is 50-100mL, the amount of sodium hydroxide is 20-50mL;

[0012] Step 2: Raw material ratio: silicon source, aluminum source, template, metal source and solvent are mixed as raw materials, and the mixture is prepared by gel preparation, crystallization reaction, washing and drying, ion exchange, modification and molding;

[0013] Step 3: Gel preparation: Slowly add silicon source and aluminum source into deionized water in sequence, stir for 30-60 minutes at 30-50°C until the mixture is evenly dispersed, then add dissolved sodium hydroxide solution dropwise, adjust the pH value of the system to 9-12, then add template, and continue stirring for 1-3 hours to form a uniform and transparent gel-like substance;

[0014] Step 4: Crystallization reaction: The obtained transparent gel-like substance is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner, the filling degree is controlled at 60%-80%, and after sealing, it is placed in a constant temperature oven and crystallized at 150-200°C for 24-72 hours;

[0015] Step 5: washing and drying: After the crystallization is completed, the autoclave is naturally cooled to room temperature, the product is taken out, and repeatedly washed with a large amount of deionized water until the pH value of the washing liquid is 7, and the solid-liquid separation process is accelerated by suction filtration to obtain the original molecular sieve powder;

[0016] Step 6: Ion exchange and modification: In order to control the acidity of the molecular sieve and the metal active center, the dried molecular sieve raw powder is immersed in a solution containing a metal salt concentration of 0.1-1 mol / L, with a solid-liquid ratio of 1:10-1:20, and stirred at 60-80°C for 3-6 hours for ion exchange, so that the metal species are stably loaded in the molecular sieve framework or pores;

[0017] Step 7: Molding: Mix the treated molecular sieve powder with an appropriate amount of binder accounting for 10%-30% of the molecular sieve mass, add a small amount of extrusion aid accounting for 1%-5% of the total mass and lubricant accounting for 0.5%-2% of the total mass, add an appropriate amount of deionized water and knead evenly, and then use an extruder to control the aperture 1-5mm or a tablet press to form a columnar or sheet-shaped catalyst body, and then dry it at 100-150°C for 12-24 hours and calcine at 400-500°C for 4-8 hours to obtain the molecular sieve catalyst used for the final polymer catalysis.

[0018] In the step 1, the silicon source is tetraethyl orthosilicate or silica sol with a purity of ≥98%, the aluminum source is aluminum nitrate, pseudo-boehmite or aluminum sulfate with a purity of ≥95% as the basic building material, the template agent is selected from quaternary ammonium salts of diethylamine, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide with a purity of ≥99%, and its amount is 0.1-0.5 times the amount of the silicon source, and an appropriate amount of sodium hydroxide is used to adjust the alkalinity of the system.

[0019] In step 3, the stirring rate is controlled at 300-500 rpm to ensure sufficient mixing.

[0020] In the step 4, during the crystallization process, the autoclave is kept under autogenous pressure, and the autoclave is gently shaken periodically every 3-6 hours to ensure uniform crystallization.

[0021] In the step 5, the crystallized raw material is placed on the filter cake, and the filter cake is placed in a vacuum drying oven and dried for 12-24 hours at 80-120° C. and a vacuum degree of ≥0.09 MPa.

[0022] In the step six, the dried molecular sieve raw powder is immersed in nickel nitrate, cobalt nitrate and palladium chloride.

[0023] In step six, the molecular sieve raw powder is repeatedly washed and dried, and then calcined in a muffle furnace at 400-600° C. for 3-6 hours to stably load it in the molecular sieve framework or pores.

[0024] In the step seven, the binder is selected from pseudo-boehmite or silica sol.

[0025] In the step 7, the small amount of extrusion aid is sesbania powder.

[0026] In the step seven, the lubricant is stearic acid.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The silicon source can be selected from tetraethyl orthosilicate or silica sol, the aluminum source can be selected from aluminum nitrate, pseudo-boehmite or aluminum sulfate, and the template agent includes quaternary ammonium salts of diethylamine, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide. The raw materials are of high purity, with the silicon source purity ≥98%, the aluminum source purity ≥95%, and the template agent purity ≥99%. This diverse selection makes it possible to customize the catalyst according to different needs. High-purity raw materials help reduce the introduction of impurities and ensure the quality and performance stability of the catalyst;

[0029] (2) The dried molecular sieve raw powder is immersed in a solution containing a metal salt, such as nickel nitrate, cobalt nitrate, or palladium chloride, with a concentration of 0.1-1 mol / L for ion exchange, with a solid-liquid ratio of 1:10-1:20, and stirred at 60-80°C for 3-6 hours, so that the metal species are stably loaded in the molecular sieve framework or pores, and then the washing and drying steps are repeated and calcined in a muffle furnace at 400-600°C for 3-6 hours, thereby enhancing the stability of the metal species in the molecular sieve and achieving effective regulation of the acidity of the molecular sieve and the metal active center, thereby optimizing the catalyst performance and improving its activity and selectivity in polymer catalytic reactions;

[0030] (3) During the molding process, pseudo-boehmite or silica sol is selected as a binder, with an amount accounting for 10%-30% of the mass of the molecular sieve, sesbania powder is used as an extrusion aid accounting for 1%-5% of the total mass, and stearic acid is used as a lubricant accounting for 0.5%-2% of the total mass. The binder is mixed with the treated molecular sieve powder, and a proper amount of deionized water is added and kneaded evenly. The mixture is then molded into a columnar or sheet-like catalyst body by an extruder or a tablet press. The catalyst is dried at 100-150° C. for 12-24 hours and calcined at 400-500° C. for 4-8 hours. The prepared catalyst has good mechanical strength and a suitable shape, is not easy to break or wear in practical applications, can maintain catalytic activity for a long time, and ensures the stability and operability of the catalyst in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the process of the preparation method of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention provides Figure 1 A method for preparing a molecular sieve catalyst for polymer catalysis, comprising:

[0034] Step 1: Raw material preparation:

[0035] Silicon source: Use ethyl orthosilicate as the silicon source, with a mass of 5-15g;

[0036] You can choose between ethyl orthosilicate (purity ≥ 98%) and silica sol (purity ≥ 98%), and the mass range is precisely anchored at 5-15g, aiming to build a solid silicon-oxygen skeleton foundation for the molecular sieve. High-quality silicon source ensures that the basic structure of the material is regular and orderly, laying a solid foundation for subsequent catalytic performance;

[0037] Aluminum source: Aluminum nitrate, with a mass of 2-10g;

[0038] Aluminum nitrate (purity ≥ 95%), pseudo-boehmite (purity ≥ 95%) or aluminum sulfate (purity ≥ 95%) can be selected as the aluminum source, with the quality controlled at 2-10g. The clever integration of aluminum elements can moderately adjust the acidity of the molecular sieve and the charge distribution of the framework, and cooperate with the silicon source to carve the internal micro-environment;

[0039] Template agent: organic amine compounds such as diethylamine are selected, with a mass of 1-10g;

[0040] High-quality quaternary ammonium salt compounds such as diethylamine, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide (purity ≥ 99%) are accurately selected, and the dosage is precisely adjusted according to the amount of silicon source material, 0.1-0.5 times, just like a "mold" to guide the molecular sieve to crystallize into a specific pore structure, paving an ideal path for the entry and exit of catalytic reaction substrates and the exposure of active sites;

[0041] Metal source: transition metal source such as sodium chromate or ammonium molybdate, with a mass of 0.1-2g, used to adjust the activity of the catalyst;

[0042] Introduce transition metal sources such as sodium chromate or ammonium molybdate (mass 0.1-2g), and then undergo a series of treatments to achieve precise anchoring of metal species in the molecular sieve, just like an "active additive" to flexibly adjust the overall catalytic activity and selectivity, in line with the "individual" needs of different polymer reactions;

[0043] Solvent: deionized water and sodium hydroxide, the amount of deionized water is 50-100mL, the amount of sodium hydroxide is 20-50mL;

[0044] Deionized water (dosage 50-100mL) serves as the main dispersion and dissolution medium, and sodium hydroxide solution (dosage 20-50mL) is used for fine adjustment of the alkalinity of the system. The two work together to create a suitable chemical environment for raw material mixing and reaction.

[0045] Step 2: Raw material ratio: silicon source, aluminum source, template, metal source and solvent are mixed as raw materials, and the mixture is prepared by gel preparation, crystallization reaction, washing and drying, ion exchange, modification and molding;

[0046] Step 3: Gel preparation: Slowly add silicon source and aluminum source into deionized water in sequence, stir for 30-60 minutes at 30-50°C until the mixture is evenly dispersed, then add dissolved sodium hydroxide solution dropwise, adjust the pH value of the system to 9-12, then add template, and continue stirring for 1-3 hours to form a uniform and transparent gel-like substance;

[0047] Step 4: Crystallization reaction: The obtained transparent gel-like substance is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner, the filling degree is controlled at 60%-80%, and after sealing, it is placed in a constant temperature oven and crystallized at 150-200°C for 24-72 hours;

[0048] Step 5: washing and drying: After the crystallization is completed, the autoclave is naturally cooled to room temperature, the product is taken out, and repeatedly washed with a large amount of deionized water until the pH value of the washing liquid is 7, and the solid-liquid separation process is accelerated by suction filtration to obtain the original molecular sieve powder;

[0049] Step 6: Ion exchange and modification: In order to control the acidity of the molecular sieve and the metal active center, the dried molecular sieve raw powder is immersed in a solution containing a metal salt concentration of 0.1-1 mol / L, with a solid-liquid ratio of 1:10-1:20, and stirred at 60-80°C for 3-6 hours for ion exchange, so that the metal species are stably loaded in the molecular sieve framework or pores;

[0050] Step 7: Molding: Mix the treated molecular sieve powder with an appropriate amount of binder accounting for 10%-30% of the molecular sieve mass, add a small amount of extrusion aid accounting for 1%-5% of the total mass and lubricant accounting for 0.5%-2% of the total mass, add an appropriate amount of deionized water and knead evenly, and then use an extruder to control the aperture 1-5mm or a tablet press to form a columnar or sheet-shaped catalyst body, and then dry it at 100-150°C for 12-24 hours and calcine at 400-500°C for 4-8 hours to obtain the molecular sieve catalyst used for the final polymer catalysis.

[0051] In the step 1, the silicon source is tetraethyl orthosilicate or silica sol with a purity of ≥98%, the aluminum source is aluminum nitrate, pseudo-boehmite or aluminum sulfate with a purity of ≥95% as the basic building material, the template agent is selected from quaternary ammonium salts of diethylamine, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide with a purity of ≥99%, and its amount is 0.1-0.5 times the amount of the silicon source, and an appropriate amount of sodium hydroxide is used to adjust the alkalinity of the system.

[0052] In step 3, the stirring rate is controlled at 300-500 rpm to ensure sufficient mixing.

[0053] In the step 4, during the crystallization process, the autoclave is kept under autogenous pressure, and the autoclave is gently shaken periodically every 3-6 hours to ensure uniform crystallization.

[0054] In the step 5, the crystallized raw material is placed on the filter cake, and the filter cake is placed in a vacuum drying oven and dried for 12-24 hours at 80-120° C. and a vacuum degree of ≥0.09 MPa.

[0055] In the step six, the dried molecular sieve raw powder is immersed in nickel nitrate, cobalt nitrate and palladium chloride.

[0056] In step six, the molecular sieve raw powder is repeatedly washed and dried, and then calcined in a muffle furnace at 400-600° C. for 3-6 hours to stably load it in the molecular sieve framework or pores.

[0057] In the step seven, the binder is selected from pseudo-boehmite or silica sol.

[0058] In the step 7, the small amount of extrusion aid is sesbania powder.

[0059] In the step seven, the lubricant is stearic acid.

[0060] Example 1: Tetraethyl orthosilicate (mass 10 g) was selected as the silicon source, aluminum nitrate (mass 6 g) was selected as the aluminum source, tetrapropylammonium hydroxide (0.3 times the amount of the silicon source) was used as the template, sodium chromate (mass 1 g) was used as the metal source, deionized water (80 mL) and sodium hydroxide (30 mL) were added, and the catalyst was prepared according to the above steps and applied to polyethylene polymerization reaction. The activity, selectivity and reusability performance data were recorded in detail and plotted into tables and curves for intuitive presentation.

[0061] Example 2: The silicon source was switched to silica sol (mass 12 g), the aluminum source was replaced with pseudo-boehmite (mass 8 g), the template agent was diethylamine (0.2 times the amount of the silicon source), the metal source was ammonium molybdate (mass 1.5 g), the crystallization temperature was adjusted to 180°C, the time was 48 hours and other parameters were fine-tuned, and the polypropylene degradation reaction was put into "trial", the catalytic performance was deeply analyzed and compared with Example 1 to analyze the similarities and differences, and the applicable boundaries and optimization directions of the process were continuously expanded (multiple embodiments can be laid out according to this logic to fully verify the practicality, stability and flexibility of the invention).

[0062] Table 1 is a table showing the experimental results of the specific polymer catalytic reaction performance comparison between the molecular sieve catalyst for polymer catalysis prepared by the present invention and the molecular sieve catalyst for conventional polymer catalysis.

[0063]

[0064] It can be seen from the table data that in a specific polymer catalytic reaction, the specific value of the catalyst conversion rate obtained by the preparation method of the present invention is 2%, which is higher than the specific value of 1% of the traditional preparation method, and the specific value of the selectivity is 4%, which is also better than the specific value of 3% of the traditional method. This shows that the catalyst of the present invention has obvious advantages in activity and selectivity, and can more effectively convert raw materials into target products and reduce the generation of by-products.

[0065] Table 2 is a table showing the experimental results of comparing the specific polymer catalytic crystal structure characteristics of the molecular sieve catalyst for polymer catalysis prepared by the present invention and the molecular sieve catalyst for conventional polymer catalysis.

[0066]

[0067] In terms of crystal structure characteristics, the molecular sieve crystal prepared by the present invention has a high crystallinity of 7% and a specific surface area of ​​9m 2 / g is larger, and the pore size distribution of 3nm is more conducive to the diffusion of reactants and products. Higher crystallinity helps to improve the stability of the catalyst, the larger specific surface area provides more active sites, and the appropriate pore size distribution speeds up the material transfer rate during the reaction. These factors jointly promote the improvement of catalyst performance.

[0068] Table 3 is a table showing the experimental results of the comparison of the parameters of the specific polymer catalytic preparation process of the molecular sieve catalyst for polymer catalysis prepared by the present invention and the molecular sieve catalyst for conventional polymer catalysis.

[0069]

[0070]

[0071] From the perspective of parameters related to the preparation process, the raw material cost of the preparation method of the present invention is 7 yuan / kg, which is lower than the traditional method of 9 yuan / kg, mainly due to the reasonable selection of raw materials and the optimization of raw material ratios. The preparation cycle of 9h is significantly shorter than the traditional method of 11h. Due to the process optimization of the present invention in the steps of gel preparation and crystallization reaction, the reaction efficiency is improved. The energy consumption of 10kW·h / kg is also lower than the traditional method of 13kW·h / kg, which is of great significance for large-scale industrial production and helps to reduce production costs and reduce the impact on the environment.

[0072] Preparation method of molecular sieve catalyst for polymer catalysis:

[0073] Select appropriate silicon source as ethyl orthosilicate, purity ≥98%, aluminum source as aluminum nitrate, purity ≥95%, template agent as diethylamine, purity ≥99%, the dosage is 0.1-0.5 times of the amount of silicon source, metal source as sodium chromate, mass 0.1-2g to adjust the activity, and solvent deionized water 50-100mL and sodium hydroxide 20-50mL, mix in a specific ratio to provide basic substances for subsequent reactions;

[0074] The silicon source and the aluminum source are slowly added to deionized water, and stirred at 40°C and 400 rpm for 45 minutes to form a mixed solution, so that the raw materials are initially dispersed evenly, and sodium hydroxide solution is added dropwise to adjust the pH to 10 to provide an alkaline environment to promote the reaction, and then the template is added and stirred for 2.5 hours to form a uniform and transparent gel-like substance, in which the template plays a structural guiding role and affects the pore structure of the molecular sieve;

[0075] The gel was transferred to a stainless steel autoclave with a polytetrafluoroethylene liner, the filling degree was controlled to be 80%, and after being sealed, it was placed in a 200°C constant temperature oven for crystallization for 72 hours. The autoclave was subjected to self-generated pressure and was shaken slightly at regular intervals (every 5.5 hours) to ensure uniform crystallization, so that the raw materials could undergo a crystallization reaction under high temperature and pressure to generate molecular sieve crystals;

[0076] After crystallization, the mixture is cooled naturally, washed repeatedly with a large amount of deionized water until the pH of the washing solution is close to 7 to remove impurity ions, and filtered to accelerate solid-liquid separation to obtain molecular sieve raw powder. The crystallized raw material is then placed on the filter cake and dried in a vacuum drying oven at 120°C and a vacuum degree of ≥0.09MPa for 24 hours to further remove moisture and residual impurities;

[0077] The dried molecular sieve raw powder is immersed in a 1 mol / L solution containing metal salts such as nickel nitrate, cobalt nitrate, palladium chloride (solid-liquid ratio 1:10-1:20), stirred at 80°C for 5 hours for ion exchange, so that the metal species are loaded in the molecular sieve framework or pores, and then the washing and drying steps are repeated, and then calcined in a muffle furnace at 600°C for 6 hours to enhance the stability of the metal species and regulate the acidity of the molecular sieve and the metal active center;

[0078] The treated molecular sieve powder is mixed with a binder (pseudo-boehmite or silica sol, with an amount accounting for 20% of the molecular sieve mass), an extrusion aid (sesbania powder, accounting for 5% of the total mass), and a lubricant (stearic acid, accounting for 2% of the total mass), and a proper amount of deionized water is added to knead the mixture evenly. The mixture is formed into a columnar or sheet-like catalyst body by an extruder or a tablet press, and finally dried at 150° C. for 24 hours and calcined at 500° C. for 8 hours to obtain the final product. The binder shapes the molecular sieve powder, the extrusion aid facilitates the molding process, and the lubricant reduces friction.

[0079] The present invention, the undescribed parts are prior art.

[0080] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a molecular sieve catalyst for polymer catalysis, characterized in that: include: Step 1: Raw material preparation: Silicon source: Use ethyl orthosilicate as the silicon source, with a mass of 5-15g; Aluminum source: Aluminum nitrate, with a mass of 2-10g; Template agent: organic amine compound, with a mass of 1-10g; Metal source: transition metal source such as sodium chromate or ammonium molybdate, with a mass of 0.1-2g, used to adjust the activity of the catalyst; Solvent: deionized water and sodium hydroxide, the amount of sodium hydroxide is 20-50mL, and the balance is deionized water; Step 2: Raw material ratio: silicon source, aluminum source, template, metal source and solvent are mixed as raw materials, and the mixture is prepared by gel preparation, crystallization reaction, washing and drying, ion exchange, modification and molding; Step 3: Gel preparation: Slowly add silicon source and aluminum source into deionized water in sequence, stir for 30-60 minutes at 30-50°C until the mixture is evenly dispersed, then add dissolved sodium hydroxide solution dropwise, adjust the pH value of the system to 9-12, then add template, and continue stirring for 1-3 hours to form a uniform and transparent gel-like substance; Step 4: Crystallization reaction: The obtained transparent gel-like substance is transferred to a stainless steel autoclave with a polytetrafluoroethylene liner, the filling degree is controlled at 60%-80%, and after sealing, it is placed in a constant temperature oven and crystallized at 150-200°C for 24-72 hours; Step 5: washing and drying: After the crystallization is completed, the autoclave is naturally cooled to room temperature, the product is taken out, and repeatedly washed with a large amount of deionized water until the pH value of the washing liquid is 7, and the solid-liquid separation process is accelerated by suction filtration to obtain the original molecular sieve powder; Step 6: Ion exchange and modification: In order to control the acidity of the molecular sieve and the metal active center, the dried molecular sieve raw powder is immersed in a solution containing a metal salt concentration of 0.1-1 mol / L, with a solid-liquid ratio of 1:10-1:20, and stirred at 60-80°C for 3-6 hours for ion exchange, so that the metal species are stably loaded in the molecular sieve framework or pores; Step 7: Molding: Mix the treated molecular sieve powder with an appropriate amount of binder accounting for 10%-30% of the molecular sieve mass, add a small amount of extrusion aid accounting for 1%-5% of the total mass and lubricant accounting for 0.5%-2% of the total mass, add an appropriate amount of deionized water and knead evenly, and then use an extruder to control the aperture 1-5mm or a tablet press to form a columnar or sheet-shaped catalyst body, and then dry it at 100-150°C for 12-24 hours and calcine at 400-500°C for 4-8 hours to obtain the molecular sieve catalyst used for the final polymer catalysis.

2. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In the step 1, the silicon source is tetraethyl orthosilicate or silica sol with a purity of ≥98%, the aluminum source is aluminum nitrate, pseudo-boehmite or aluminum sulfate with a purity of ≥95% as the basic building material, the template agent is selected from quaternary ammonium salts of diethylamine, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide with a purity of ≥99%, and its usage is 0.1-0.5 times the mass of the silicon source, and sodium hydroxide is used to adjust the alkalinity of the system.

3. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In step 3, the stirring rate is controlled at 300-500 rpm to ensure sufficient mixing.

4. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In the step 4, during the crystallization process, the autoclave is kept under autogenous pressure, and the autoclave is gently shaken periodically every 3-6 hours to ensure uniform crystallization.

5. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In the step 5, the crystallized raw material is placed on the filter cake, and the filter cake is placed in a vacuum drying oven and dried for 12-24 hours at 80-120° C. and a vacuum degree of ≥0.09 MPa.

6. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In the step six, the dried molecular sieve raw powder is immersed in nickel nitrate, cobalt nitrate and palladium chloride.

7. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In step six, the molecular sieve raw powder is repeatedly washed and dried, and then calcined in a muffle furnace at 400-600° C. for 3-6 hours to stably load it in the molecular sieve framework or pores.

8. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In the step seven, the binder is selected from pseudo-boehmite or silica sol.

9. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In the step 7, the small amount of extrusion aid is sesbania powder.

10. The method for preparing a molecular sieve catalyst for polymer catalysis according to claim 1, characterized in that: In the step seven, the lubricant is stearic acid.